Exploring the Link Between Product Innovation and Firm Performance: Empirical Insights from Energy Enterprises in Yunnan, China - Yinyin, Wan (Scholar: Human Sciences, 2025)
Purpose: This study aims to construct a comprehensive theoretical framework to test the influence of key resource factors within the frameworks of the Resource-Based View (RBV) and Customer Relationship Management (CRM) theories on product innovation and firm performance. Data and Methodology: Based on RBV and CRM theories, this research collected 516 data samples through a questionnaire survey from photovoltaic state-owned enterprises (SOEs) in Yunnan, China. The data were analyzed using Structural Equation Modeling (SEM). Results: The findings confirm that all hypotheses are supported. Creativity Capability, Information Sharing, Top Management Support, Customer Involvement, and Institutional Support have a direct significant impact on Product Innovation Capability and an indirect significant impact on Firm Performance. Among these factors, CC has the highest impact on product innovation, followed by IST, TMS, CI, and IS. Conclusion: This study enriches the empirical data on photovoltaic SOEs in Yunnan, providing valuable management suggestions for optimizing resource allocation, enhancing innovation capability, and improving market competitiveness. The findings also highlight the crucial role of government policy support in promoting high-quality development of the photovoltaic industry in China. By providing a systematic theoretical framework and empirical evidence, this research aims to help enterprises and policymakers understand and address innovation challenges in the photovoltaic industry, achieving sustainable development and long-term competitiveness.